Jane Austen. the critical heritage - Southam, B. C. (Critical heritage series., 1995)
The Critical Heritage gathers together a large body of critical sources on major figures in literature. Each volume presents contemporary responses to a writer's work, enabling student and researcher to read the material themselves.